RWA: Optical Networks with Heuristics Algorithms (2016)
The increase in demand for data transport through WDM (Wavelength Division Multiplexing) networks has led to the emerging problems related to finding routes and assigning wavelengths in these networks, which are solved through algorithmic processes. Conventional algorithms only satisfy the conditions of static traffic. However, the heuristic algorithms may be processed in dynamic traffic scenarios. This paper proposes a comprehensive strategy to address DLE (Dynamic Lightpath Establishment), i.e., without dividing the problem, using several heuristic algorithms. The results shown indicate that the heuristic algorithms respond better under stress in dynamic scenarios, but with high network use.